2007
DOI: 10.1002/elan.200603785
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐ and Nano‐ Magnetic Particles for Applications in Biosensing

Abstract: This article reviews the development of electrochemical biosensors, incorporating magnetic particles, for detecting biomolecules (nucleic acids and proteins) and cells. Magnetic particles (MPs) of micro-and nanoscale, mimicking the size of molecules in nature, possess interesting characteristics that facilitate the purification and detection of biomolecules in a wide range of samples. In particular, the high surface area and the paramagnetic or superparamagnetic properties of these tiny particles provide an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
132
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(133 citation statements)
references
References 162 publications
0
132
0
1
Order By: Relevance
“…It has been reported that nanomaterials possess insecticidal properties (Simonian et al 2005;Biju 2007;Rai et al 2012;Chakravarthy et al 2012). Furthermore, metal nanoparticles are essential components of new biosensors and self--assembled nanodevices (Levy et al 2006;Hsing et al 2007;Bhattacharyya et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that nanomaterials possess insecticidal properties (Simonian et al 2005;Biju 2007;Rai et al 2012;Chakravarthy et al 2012). Furthermore, metal nanoparticles are essential components of new biosensors and self--assembled nanodevices (Levy et al 2006;Hsing et al 2007;Bhattacharyya et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Also, they are employed in magnetic separation, drug carrier, magnetic resonance imaging (MRI), hyperthermic therapy, etc. 1 Although a number of literatures have been reported on the preparation of magnetic particles, most of them emphasized on iron alloys and iron oxide particles. [2][3][4][5] The reports on zero-valent iron Fe(0) magnetic particles are relatively limited in spite of their better magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In microfluidics, core-shell catalyst particles can be synthesized consisting of a magnetic core and a catalytic shell. These magnetically controlled particles have been used for cell manipulation, microscopic drug delivery and in microsensor applications [9][10][11]. Antibody coated magnetic microparticles have also been used in the capture of target species flowing in a 75 μm wide micro channel [12].…”
Section: Introductionmentioning
confidence: 99%